Assessing Alternative Techniques for Scaling the Family Leisure Activity Profile: Recommendations for Future Family Leisure Measurement. (14th March 2016) - Melton, Karen K.; Ellis, Gary; Zabriskie, Ramon
ABSTRACT: Psychometric properties of the Family Leisure Activity Profile (FLAP) were evaluated using family leisure and family functioning ratings from 884 parents and children residing in the United Kingdom. Review and critique of the FLAP resulted in identification and evaluation of three alternative scaling techniques. Scaling Technique 1 was current practice, Technique 2 focused on family leisure environments rather than family leisure activities, and Technique 3 involved generating an estimate of duration of participation in family leisure in natural units of time. Inter-rater agreement and reliability were strong for all three scaling techniques. Technique 3 yielded the best model fit. Empirical relations with family functioning variables were consistent with predictions, yet none of the scaling techniques resolved a longstanding problem regarding specific relations among core and balance patterns of participation, family cohesion, and family adaptability. Suggestions for improving the FLAP are provided.